1996
DOI: 10.1093/carcin/17.12.2655
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of exposure to acrylonitrile by determination of N-(2-cyanoethyl)valine at the N-terminal position of haemoglobin

Abstract: A selected ion monitoring gas chromatography-mass spectrometry (GC-MS) procedure was developed to determine the interaction product formed by acrylonitrile (ACN) with the N-terminal amino group in haemoglobin. The product, N-(2-cyanoethyl)valine (CEV), was analysed following its release from the protein by a modified Edman degradation procedure. Quantitation was achieved using N-(2-cyanoethyl)-[2H8]Val-Leu-Ser as internal standard. The limit of detection of the assay was 1 pmol CEV/g globin. A close to linear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 20 publications
1
13
0
1
Order By: Relevance
“…Nevertheless, the adduct ratio between smokers and non-smokers remains consistent across all those studies (3- to 5-fold increase in smokers compared to non-smokers). The mean CEVal value in our study (133 pmol/g Hb) was similar to another study showing mean levels of 112 pmol/g Hb for 264 smokers and 6.5 pmol/g Hb for 100 non-smokers (Scherer et al, 2007) and half of what was reported in an earlier assessment (217 pmol/g Hb) in pregnant smoking mothers (Tavares et al, 1996). However, this study was conducted in a relatively small group of 13 heavy smoker females and the ISO Tar yield of the product was not specified.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Nevertheless, the adduct ratio between smokers and non-smokers remains consistent across all those studies (3- to 5-fold increase in smokers compared to non-smokers). The mean CEVal value in our study (133 pmol/g Hb) was similar to another study showing mean levels of 112 pmol/g Hb for 264 smokers and 6.5 pmol/g Hb for 100 non-smokers (Scherer et al, 2007) and half of what was reported in an earlier assessment (217 pmol/g Hb) in pregnant smoking mothers (Tavares et al, 1996). However, this study was conducted in a relatively small group of 13 heavy smoker females and the ISO Tar yield of the product was not specified.…”
Section: Discussionsupporting
confidence: 91%
“…For instance, only a moderate linear correlation was found between 4-ABP-Hb and plasma cotinine (ng/ml; L R 2 33%; Maclure et al, 1990), which is very similar to the value we obtained when performing a linear correlation between 4-ABP-Hb and 4-ABP (expressed in ng/L; L R 2 30%) or 4-ABP-Hb with TNEQ (µg/mL; R 2 24%). A moderate correlation ( L R 2 40%) was reported for acrylonitrile haemoglobin adducts and CPD in the Tavares et al’s (1996) study. In our study, a similar comparison gave only a 19% correlation, but our smoker group was much larger.…”
Section: Discussionmentioning
confidence: 76%
“…Full details of this analytical procedure will be reported elsewhere [12]. As an example of the approach, Figure 5 depicts the GC-MS selected ion recording traces for three N-(2-cyanoethyl)valine determinations.…”
Section: Resultsmentioning
confidence: 99%
“…The procedure for the Edman degradation of this protein is described in detail elsewhere [12] and, in summary, involves:…”
Section: Edman Degradation Proceduresmentioning
confidence: 99%
“…5 Analytical studies have found elevated levels of tobacco-specific mutagens or cotinine in amniotic fluid, fetal urine, or fetal blood from smoking mothers compared with nonsmoking mothers, 5-9 providing direct evidence of the presence of such compounds in utero. Protein adducts of tobacco-specific compounds have been identified in cord blood, [10][11][12] indicating that such compounds interact covalently with fetal macromolecules, with potentially mutagenic consequences.…”
Section: Smoking While Pregnantmentioning
confidence: 99%